Exploring Contraceptive Use Among Reproductive Woman at Pamekasan, Madura Island - Dwi Jayanti, Ratna; Ivon Diah Wittiarika; Agnestia Naning Dian Lovita; Euvanggelia Dwilda Ferdinandus; Nurul Azizah; Rafhani Rosyidah; Pionera Seconda Giyanti Putri (Rifa'Institute, 2026)
Introduction: Unintended pregnancy remains a major global and national concern, with 64 unintended pregnancies per 1,000 women worldwide and 15.5% of pregnancies in Indonesia reported as unwanted; the Indonesian government addresses this issue through the Family Planning program, where contraceptive use has reached 62.38% nationally. Even while long-term methods like IUDs and implants are very effective, their use is still inconsistent, whereas short-term like injectable contraception is most often used. Objective: this study aimed to exploring contraceptive use among reproductive woman at rural area. Method: A cross-sectional study using consecutive sampling involved 69 women of reproductive age completing structured questionnaires on contraceptive use, analyzed using descriptive statistics. Result and Discussion: Most respondent in 40-49 group age (42%), have secondary education level (57%), have no working (77%), and Married woman (91%). Most participants (54.4%) not used contraception although 74% ever used contraception, with the hormone injection were the preferred contraceptive methods. Conclusions: This study show a sociodemographic characteristic that can be analyzed in the future study.